2018
DOI: 10.1002/cpns.53
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pain Avoidance‐Like Behavior in Drug‐Dependent Rats

Abstract: In contrast to their analgesic properties, excessive use of either opioids or alcohol produces a paradoxical emergence of heightened pain sensitivity to noxious stimuli, termed hyperalgesia, which may promote increased use of opioids or alcohol drinking to manage worsening pain symptoms. Hyperalgesia has traditionally been measured in rodents via reflex-based assays, including the von Frey method. To better model the motivational and affective dimensions of pain in a state of opioid/alcohol dependence and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Mechanical allodynia is a robust method for measuring hyperalgesia during nicotine withdrawal (Carstens, Anderson et al 2001, Cohen, Treweek et al 2015, Hamouda, Jackson et al 2018, Pahng and Edwards 2018, Xue, Kallupi et al 2018). In the present study, a reduction of hyperalgesia was observed at all the doses of CBD tested during acute withdrawal and protracted abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical allodynia is a robust method for measuring hyperalgesia during nicotine withdrawal (Carstens, Anderson et al 2001, Cohen, Treweek et al 2015, Hamouda, Jackson et al 2018, Pahng and Edwards 2018, Xue, Kallupi et al 2018). In the present study, a reduction of hyperalgesia was observed at all the doses of CBD tested during acute withdrawal and protracted abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…The tail‐flick and hot‐plate tests are most commonly used to evaluate the analgesic efficacy of drugs, whereas the Hargreaves and von Frey tests are used to evaluate both analgesia and pain‐like states (hyperalgesia/allodynia). However, based on the considerable lack of translational efficacy of putative analgesics as examined via these preclinical methods, many researchers are now transitioning away from reflex‐based assays toward more cognitive and motivational tasks that are thought to be more related to the negative affective components of pain (e.g., Pahng and Edwards, ; Tappe‐Theodor et al, ).…”
Section: Preclinical Models To Investigate the Intersection Of Aud Anmentioning
confidence: 99%
“…Finally, as mentioned above the motivational and affective components of pain have started to be more thoroughly investigated in rodent models. A potential model for this purpose was recently described by Pahng and Edwards (). This model incorporates a non–reflex‐based method to measure pain avoidance‐like behavior in rats.…”
Section: Preclinical Models To Investigate the Intersection Of Aud Anmentioning
confidence: 99%
“…These non-reflexive-based assays allow the potential to examine the contribution of negative affective-like states towards activity avoidance and pain interference in the context of SUD. 47 , 48 In the mechanical conflict-avoidance system (MCS) task, animals traverse mechanically noxious probes of varying heights to avoid a bright aversive light, escaping to reach a goal chamber that is dark. A longer latency to exit onto the probes reflects increased pain avoidance-like behavior as a motivational correlate of hyperalgesia.…”
Section: Animal Models To Examine Pain and Sud Interactionsmentioning
confidence: 99%
“…The specific strengths and limitations of the MCS procedure have been described, illustrating its utility in measuring both analgesic and hyperalgesic conditions. 47 , 49 , 50 Another innovative technique in this area is the Orofacial Pain Assessment Device (OPAD), which pairs a thermal stimulus conflict with access to an appetitive reward 51 and can be readily applied to oral alcohol or opioid self-administration. These reflex-based and non-reflex-based pain assays can be used in tandem to more comprehensively examine the effects of opioid and alcohol dependence on both somatic and affective pain-like behaviors in rodents.…”
Section: Animal Models To Examine Pain and Sud Interactionsmentioning
confidence: 99%